The development of in vitro human fibroblast feeder line - Mat Yusof, Afzan; Md Isa, Muhammad Lokman (2017)
Human embryonic stem cells (hESCs) need feeder cells for their maintenance in an undifferentiated state. In conventional culture systems, mouse embryonic fibroblasts (MEFs) serve as feeder cells to maintain hESCs. These cells are pluripotent, immortal, and they retain their developmental potential after prolonged culture and maintain normal karyotypes after continuous culture. Given the outstanding potential of human ES cell lines, their availability offers a unique and novel research tool with prospective widespread clinical applications. Human ES cells may be utilized in the future in various research areas, such as human developmental biology, teratology, and cell-based therapies. Contrary to human ES, mouse ES cells can be grown directly on gelatin-coated plates with the addition of leukemia inhibitory factor. Handling the simultaneous growth of both ES cells and MEF requires meticulous care and may prove to be rather expensive. In addition, the dual growth of these cells exposes the human ES cells to mouse retroviruses, which may prevent their future use in cell-based therapy, thus limits the potential of hESCs in cell replacement therapy. Consequently, the use of human feeder cells would be an important step forward in this in vitro technology. Therefore, objectives of this research were to prepare feeder culture by using human fibroblast, to stabilize human fibroblast feeder culture from being contaminated and to observe the changes that occur on human fibroblast feeder culture after undergoing 5-10 passages. The biopsy tissue was obtained from IVF Centre IIUM of normal patient undergo IVF treatment with consent. It was found there was no contamination in term of pathogens after human fibroblast feeder culture is being stabilized. It is also found that there were no significant changes on human fibroblast feeder culture after undergoing 5-10 passages.